Dissecting leadership education and assessment in surgery. Issue 1164 (30th April 2021) - Morad, Raimand; Kumar, Hemant; Snelling, Iain
Abstract: The importance of leadership is well recognised within surgery owing to the heavily teamwork dependent nature and uniquely dynamic working environment of the operating room. Teaching and assessment methods of leadership within UK surgical training has arguably lacked credence in comparison to the more tangible technical clinical competencies due to the fact that the daily tasks of surgeons are multifaceted and cannot be simplified into a tick-box exercise. As such, some surgical trainees perceive themselves to be minimally competent in their leadership ability. The new surgical curricula planned to be implemented by the Intercollegiate Surgical Curriculum Programme in August 2021 aims to address this by shifting leadership training and assessment towards an outcome-based approach, rather than a competency-based approach, with an emphasis on the role of the professional judgement of trainers as well as trainee self-reflection. This article explores these proposed changes by framing them within the context of the wider literature pertaining to surgical leadership education.